Development of a risk management method for development projects of providers of housing and utility services - Chernenko, Yuri; Haidaienko, Oksana; Tkachenko, Valentyn (Technology audit and production reserves, 2022)
The object of research in the work is the processes of anti-risk management of projects for the development of providers of housing and utility services (PHUS). Particular attention is required to limit the management of the activities of the PHUS, related to the specifics of the housing and utility services sector. They have a significant impact on the need for the PHUS to constantly adjust the direction of efforts. They force companies to constantly monitor the progress of their projects and redirect resources. The priority should be development projects with the highest and fastest financial results with minimal risks. An essential lever for improving the effectiveness of anti-risk management in the projects for the development of PHUS is the possibility of adjusting the priorities for the implementation of these projects as much as possible in real time. This study developed a method of anti-risk management of development projects for housing and utility services providers, which consists in integrating such approaches into a single process, such as the implementation of management automation and decision-making algorithms. As well as the implementation of a process approach in risk management and decision making; implementation of benchmarking; and building a dynamic organizational structure for managing development projects The scheme of the method of anti-risk management of projects for the development of housing and utility services providers includes the following steps: – formation of a register of projects for the development of providers of housing and utility services; – identification of limitations of projects for the development of providers of housing and utility services; – implementation of automation of management and algorithmization of decision-making in the management of projects for the PHUS development; – application of a process approach in risk management and decision-making in the management of projects for the PHUS development; – building a dynamic organizational structure for managing development projects; – implementation of benchmarking in the management of projects for the PHUS development; – adjusting the PHUS priorities for the implementation of development projects in real time; – increasing the effectiveness of anti-risk management by directing the main resources to the PHUS development projects with minimal risks and the most significant economic result. The integration of all the above blocks into the anti-risk management of PHUS development projects makes it possible to increase the efficiency of managing these projects by directing the main resources to them with minimal risks and the most significant economic result. This, in turn, will improve the performance of providers of housing and utility services in terms of increasing income and reducing costs.